Mathematical modeling of fixed and declining amortization schemes in cooperative loan systems - Werry Febrianti; Ainol Yaqin (Scientific Nexus, 2025)
Village cooperatives play a pivotal role in promoting rural economic development by providing accessible microfinance services. This study evaluates two widely applied loan amortization schemes—fixed installment (annuity) and declining balance—within the framework of cooperative finance. By simulating a 12-month loan of IDR 10,000,000 at a 1% monthly interest rate, the paper models and examines the allocation of principal and interest payments under both approaches. The results indicate that although fixed installments ensure stable monthly obligations, they generate higher cumulative interest costs compared to declining balance schemes, which more closely align repayment amounts with the outstanding loan balance. A sensitivity analysis of varying interest rates and loan tenors further offers insights into financial risk management and borrower affordability. These findings can help cooperative managers develop more effective and transparent lending strategies.